Characteristics of boar semen preserved at liquid state. Issue 1 (1st January 2017) - Karunakaran, M.; Chakurkar, E. B.; Ratnakaran, U.; Naik, P. K.; Mondal, M.; Mondal, A.; Singh, N. P.
ABSTRACT: Thirty semen ejaculates collected from five Large White Yorkshire boars were preserved in Beltsville thawing solution (BTS) and SAFEcell plus extenders at 16–18°C over a period of seven days. Preserved semen samples were evaluated for sperm motility, plasma membrane integrity and concentration of lipid peroxidation compound malondialdehyde (MDA) every day during storage. Semen samples preserved in the SAFEcell plus extender had significantly more per cent of sperm cells with total motility, progressive forward motility and plasma membrane integrity, significantly low level of MDA concentration than BTS extender from day 1 to day 7 of storage. It can be concluded that the SAFEcell plus extender is better than BTS to preserve boar semen in the liquid state at 16–18°C.